ANALISA PERCEPATAN PROYEK DENGAN METODE CRASHING PROGRAM PADA PROYEK PEMBANGUNAN GEDUNG AUDITORIUM IAIN KOTA AMBON (Studi Kasus : Pembangunan Gedung Auditorium IAIN Kota Ambon) - Rialyantha Matahelumual; Octovianus Jamlaay; Tonny Sahusilawane (Jurusan Teknik Sipil, 2022)
The schedule of a project is a very principal aspect in project management because it is arranged to achieve the time target of project completion and to avoid delays in the project. IAIN Ambon Auditorium Building Construction Project experienced delays in Sloof work, so it should be accelerated. By using crashing method, it can be seen how far the project duration can be accelerated with minimum additional costs. The Crashing Method determine which jobs are included in the critical path. It can be seen the crash cost of each activity on the critical path, the crash cost of each activity on the critical path, the normal total cost and the total cost after the program crash. From the data analysis result, a critical trajectory was obtained on the work of the SMK3K, Structural Work (Sloof), Work (Wall, Plasteran and Painting), Lighting and Installation Work, AC Work and Mechanical Ventilation, Fire Extinguisher Work (R. Pump Per. Main Fire Fighting, Fire Hydrant Fire Fighting) and Parking Jobs. Costs after acceleration are IDR 26,548,098,287.58 or decrease by 0.15% with an acceleration time of 126 days. The impact caused by the addition of 2 hours of overtime with a difference in costs of IDR 11,278,287.44 or an increase of 0.09% from the initial cost. When crashing the duration of the project is reduced by 9 days, which was originally 135 working days to 126 working days. Keywords: Project Scheduling, Critical Path, Crashing Program